2021
DOI: 10.1007/s10565-021-09627-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA methylation in mammalian development and cancer

Abstract: Similar to epigenetic DNA and histone modifications, epitranscriptomic modifications (RNA modifications) have emerged as crucial regulators in temporal and spatial gene expression during eukaryotic development. To date, over 170 diverse types of chemical modifications have been identified upon RNA nucleobases. Some of these post-synthesized modifications can be reversibly installed, removed, and decoded by their specific cellular components and play critical roles in different biological processes. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 166 publications
0
58
0
Order By: Relevance
“…Outside of hematopoiesis, m 6 A has been found to be a critical regulator in stem cell fate, neuronal development, and skin development. The role of m 6 A in development and stem cell biology is reviewed extensively elsewhere ( Frye et al, 2018 ; Malla et al, 2019 ; Rosselló-Tortella et al, 2020 ; Vasic et al, 2020 ; Song et al, 2021 ). Here we will summarize the role of m 6 A in differentiation in several contexts.…”
Section: The Role Of M 6 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…Outside of hematopoiesis, m 6 A has been found to be a critical regulator in stem cell fate, neuronal development, and skin development. The role of m 6 A in development and stem cell biology is reviewed extensively elsewhere ( Frye et al, 2018 ; Malla et al, 2019 ; Rosselló-Tortella et al, 2020 ; Vasic et al, 2020 ; Song et al, 2021 ). Here we will summarize the role of m 6 A in differentiation in several contexts.…”
Section: The Role Of M 6 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…Many studies have shown that the high expression of almost all m5C regulators is significantly related to the shorter overall survival period of HCC patients except for NSUN7, suggesting that the dysfunction of m5C regulators has a strong impact on HCC progression (He et al, 2021). Since then, a study used clinical information from the TCGA database to assess m5C regulator alterations and the survival rate in patients and found that the p-value of the NSUN5 and ALYREF genes in HCC is less than 0.05, as well as the significant difference in the NSUN6 gene, which provides an important basis for exploring m5C regulators as potential therapeutic targets for HCC (Song et al, 2021). Moreover, gene set enrichment analysis (GSEA) showed that the high expression of NSUN4 and ALYREF mainly affects the m5C methylation/demethylation process, cell cycle regulation and mitosis, respectively, which is closely related to the prognosis of HCC (He et al, 2020a).…”
Section: Rna 5-methylcytosine Epigenetic Modification In Hepatocellular Carcinomamentioning
confidence: 99%
“… 2 , 3 RNA methylation is one of the predominant forms of epigenetic modification, accounting for >60% of RNA modifications. 4 The common sites of RNA methylation mainly include N 6 -methyladenosine (m 6 A), 5-methylcytosine (m 5 C), N 1 -methyladenosine (m 1 A) and 7-methylguanosine (m 7 G). As the most prevalent type among these methylations, m 6 A, which describes a methylation at the N 6 position of adenosine and enriched in the consensus sequence RRACH (R: A or G; A: m 6 A; and H: A, C, or U), has become a hotspot in the research community.…”
Section: Introductionmentioning
confidence: 99%